Wage bargaining, employment, and union power: The right-to-manage approach - Volker Böhm; Oliver Claas (Bielefeld University, Center for Mathematical Economics (IMW), 2014)
This paper analyzes the implications of right-to-manage wage bargaining between a producers' syndicate and a workers' union representing finite numbers of identical members in a monetary macroeconomic model of the AS-AD type with government activity. At given prices and price expectations, nominal wages are set according to a Nash bargaining agreement. Producers then choose labor demand and commodity supply to maximize profits at given output prices. The commodity market clears in a competitive fashion. Unique temporary equilibria are shown to exist for each level of relative power of the union. These equilibria may exhibit under- or overemployment, depending on the level of union power. The paper presents a complete comparative-statics analysis of the temporary equilibrium, in particular of the role of union power on employment, wages, and income distribution, including a variety of different qualitative features compared to the situation under efficient bargaining. These differences arise primarily from a supply-side effect of union power under the right-to-manage approach as compared to a demand-side effect under efficient bargaining. In addition, the dynamic evolution under perfect foresight is monotonic with two coexisting balanced steady states, one of which is stable under certain conditions. These properties are qualitatively identical to those under efficient bargaining or under perfect competition.
urn:nbn:de:0070-pub-26753389
Keywords: C78; D61; E24; E25; E31; E42; J52; 330; Collective Bargaining; Nash Bargaining; Union Power; Aggregate Supply-Aggregate Demand; Government Deficits; Perfect Foresight; Dynamics; Stability